Eksplorasi Transaksi Derivatif Dalam Keuangan Islam - Husni Shabri (Al-bank: Journal of Islamic Banking and Finance, 2022)
This study aims to explore the application of derivative transactions in Islamic financial institutions in Indonesia, Malaysia and Pakistan. The research method uses descriptive qualitative approach with Systematic Literature Review. Data collection techniques using documentation. The results show that derivative transactions are permitted only for Future Trading on the Commodity Exchange at the Jakarta Futures Exchange which is regulated in fatwa DSN No. 82 of 2011. Derivative transactions are also allowed to hedging aims to mitigate risk in foreign exchange transactions, not for speculation. This view is also in line with the application in Malaysia and Pakistan that the practice of derivatives is only a hedging to minimize risk. The challenge faced in derivative transactions is the difficulty of operating sharia-compliant derivatives so that in the future it is hoped that there will be derivative innovations with sharia principles